Impact of Solid Waste Toxicity Generated by Pesticides - Elias Estremadoyro, Diego Fernando (2022)
This article is a bibliographic review of investigations on the toxicity exposure of a diversity of non-target organisms due to different concentrations of pesticides used in crops, but that can somehow impact certain individuals and their environment. The article presents a description of the type and grade of evaluated pesticides and their repercussions on the aquatic and terrestrial environment. Likewise, it includes a comparison of the results obtained by some authors in their experiments. It complements this information with a compilation on the impact caused due to the handling of pesticide containers, including the impact of said residues on public health. The analysis concludes that said synthetic pesticide residues, regardless of their composition, are a latent risk for the environment and public health.